SENTRALISASI ISLAM MARJINAL: Dari Dunia Melayu-Nusantara untuk Dunia Islam - Lukmanul Hakim (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Imam Bonjol Padang, 2017)
This paper aims to provide an understanding of the marginalization and centralization of Malay-Nusantara Islam and the characters who talk about it. The method used is the historical method. Marjinalization of Malay-Nusantara Islam is an attempt to see Islam in Malay-Nusantara has nothing to do with Islam in the region of the Arab World. This means that Islam in Malay-Nusantara stands alone, has nothing to do with Islam in other regions, especially Islam in the Arab world and not part of the Islamic world as a whole. Among the characters who talked about it: Landon, van Leur, Winsted, de Graaf, Snouck Hurgronje, Clifford Geertz, and Ricklefs. While the centralization of Malay-Nusantara Islam is an effort to see Islam in Malay-Nusantara as a unity that can not be separated with other areas, especially with Islam in the Arab world. It means Islam in Malay-Nusantara is part of the Islamic world as a whole. Among the characters who talk about it: S. M. N. Alatas, Hussein Alatas, Nikkie R. Keddie, William R. Roff, Anthony Reid, Anthony H. Johns and Milner, and Azyumardi Azra.